2013
DOI: 10.1097/jac.0b013e318267473b
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Risk Factors and the Likelihood of Patient-Physician Communication and Health Maintenance Services in Medicare Health Plans

Abstract: This study examined both individual and combined effects of race, education, and health-based risk factors on health maintenance services among Medicare plan members. Data were from 110 238 elderly completing the 2006 Medicare Health Outcomes Survey. Receipt of recommended patient-physician communication and interventions for urinary incontinence, physical activity, falls, and osteoporosis was modeled as a function of risk factors. Low education decreased the odds of receiving services; poor health increased o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…We extended this research to participants in Medicare Advantage programs and found that P4P incentives did not improve racial/ethnic disparities in care for urinary incontinence. Reports on disparities among Medicare Advantage participants by income and disability status (18) and by race/ethnicity (4) indicated that socioeconomically disadvantaged populations were not always less likely to receive health care services than higher-income populations. Our findings confirm previous reports that differences in quality of care by race/ethnicity were not always in the expected direction, that is, poorer for racial/ethnic minorities than for whites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We extended this research to participants in Medicare Advantage programs and found that P4P incentives did not improve racial/ethnic disparities in care for urinary incontinence. Reports on disparities among Medicare Advantage participants by income and disability status (18) and by race/ethnicity (4) indicated that socioeconomically disadvantaged populations were not always less likely to receive health care services than higher-income populations. Our findings confirm previous reports that differences in quality of care by race/ethnicity were not always in the expected direction, that is, poorer for racial/ethnic minorities than for whites.…”
Section: Discussionmentioning
confidence: 99%
“…The Centers for Medicare and Medicaid Services (CMS) collect performance data from Medicare Advantage plans using 3 data sources — the Healthcare Effectiveness Data and Information Set, Consumer Assessment of Healthcare Providers and Systems, and the Medicare Health Outcomes Survey — with 48 performance measures to assess plan performance (2). Using data from 2006, Ng and colleagues found significant differences in the delivery of preventive care services between black and white patients (4). They reported that black patients were more likely to receive care from their health care provider to reduce falls, but white patients were more likely to receive osteoporosis care.…”
Section: Introductionmentioning
confidence: 99%